Introducing Conversation Analysis (CA) for SLA - Hanafi Hanafi (LINGUA LITERA : journal of english linguistics and literature, 2016)
This paper introduces CA for SLA as the edge-cutting approach toward empirical studies in the field of SLA. Since CA for SLA is a specificcross cutting branch of Interlanguage Pragmatics and SLA, a chronological account of its birth should be preceded by an overview of both wider disciplines. The overview breaks down the strengths and shortages of those approaches in the study of language acquisition. A comprehensive review of empirical studies on each fields is also presented as a general research road map. Through this overview, the emergence of CA for SLA can be fully integrated and future research orientation can be suggested.